2014
DOI: 10.1210/jc.2013-3160
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of the Optimal Time Interval for Repeat Evaluation After a Benign Thyroid Nodule Aspiration

Abstract: An initially benign FNA confers negligable mortality risk during long-term follow-up despite a low risk of identifying several such nodules as thyroid cancer. Because such malignancies appear adequately treated despite detection at a mean 4.5 years after falsely benign cytology, these data support a recommendation for repeat thyroid nodule evaluation 2-4 years after the initial benign FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 17 publications
6
49
0
1
Order By: Relevance
“…At our institution the malignancy rate among nodules with documented growth is quite low (i.e. 1-2%), in agreement with other papers reporting thyroid lesions followed-up after an initial benign assessment [21][22][23][24]. Finally, in our series PTC/ FTC ratio was 72:1 (216/3 cases).…”
Section: Discussionsupporting
confidence: 91%
“…At our institution the malignancy rate among nodules with documented growth is quite low (i.e. 1-2%), in agreement with other papers reporting thyroid lesions followed-up after an initial benign assessment [21][22][23][24]. Finally, in our series PTC/ FTC ratio was 72:1 (216/3 cases).…”
Section: Discussionsupporting
confidence: 91%
“…The question is even how long should the follow-up be. According to Nou et al [53], who followed up 2,010 benign nodules for an average of 8.5 years (range 0.25–18), repeated thyroid nodule evaluation should be done 2–4 years after the initial benign FNA. 18 false-negative thyroid malignancies were diagnosed at a mean 4.5 years (range 0.3–10) after the initial benign biopsy.…”
Section: What Is the Evidence That Molecular Fna Diagnostics With A Gmentioning
confidence: 99%
“…However, a longer follow-up of 8.1 years was proposed by Liel et al [55]. Based on the data of Nou et al [53] a 2-year follow-up should be sufficient.…”
Section: What Is the Evidence That Molecular Fna Diagnostics With A Gmentioning
confidence: 99%
“…Several recent studies have confirmed that the ROM is very low for this category [4,21,22]. Risk stratification based upon ultrasound patterns (ATA 2015 revised guidelines) can be used to guide clinical follow-up of thyroid nodules with benign cytology [4].…”
Section: Specific Issues Pertaining To the Different Diagnostic Categmentioning
confidence: 99%